Shifts in Korean Television Music Programmes: Democratization, Transnationalization, Digitalization - Jung, Sun (Television Histories in Asia: Issues and Contexts, 2015)
Korea was the fifteenth country in the world to start television broadcasting when it first launched in Seoul in 1956. Since then, the structure, content and policies concerning Korean television have continuously transformed, due largely to changing contextual circumstances such as wide-ranging socio-political democratization and the rise of the neoliberal global economic system and digital technologies. Up until the 1980s, the oligopolistic structure of the two public broadcasting networks  – Korean Broadcasting System (KBS) and Munhwa Broadcasting Corporation (MBC)  – dominated the broadcasting market. However the landscape has dramatically changed since the early 1990s, with 11 newly launched commercial terrestrial broadcasting channels (including Seoul Broadcasting System (SBS) in December 1991) and 153 cable channels when the multichannel television era began (Jin 2005 : 1). A digital satellite television system called Skylife was launched in March 2002, and airs 176 channels at the time of writing. Such changes stem from the shift in the domestic political climate where liberalization and privatization were promoted in assertively practiced neoliberal reform movement in the early 1980s, as well as changes in the global cultural industry environments based largely on globalization and the development of digital technologies. This chapter explores democratization, transnationalization and digitalization, three active factors within Korean television broadcasting by analysing changes and shifts in popular music programmes.
Keywords: 1-TV; 2-Approches sociologiques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude de la réception; 2-Étude des industries culturelles; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; Australie (lieu de production du savoir); Corée du Sud (corpus analysé); _Nettoyé

Globalizing Lifestyles? Makeover Television in Singapore - Lewis, Tania (The Politics of Reality Television: Global Perspectives, 2010)
The past decade has seen an explosion of lifestyle makeover television shows with audiences being urged to “renovate” everything from their homes, bodies, and children to their pets, a process that has seen the emergence of an army of lifestyle gurus on television advising us on what not to eat and what not to wear. While critical academic attention has largely focused on blockbuster reality television formats like Big Brother and Survivor, more recently a growing body of scholarship has started to focus on the “lifestyle turn” on television and the rise of the makeover format. To date much of the work on makeover television has focused on its role in the US and UK. However, in the past couple of years the lifestyle makeover show has become an increasingly global phenomenon with audiences around the world embracing everything from home renovation to plastic surgery makeover shows. This essay is concerned with examining the implications of the global dissemination of such modes of programming, associated as they are with ideologies of neoliberal individualism, self-surveillance and self-promotion, and with a strongly consumption-oriented aesthetic. It emerges out of a pilot study I have been conducting with Dr Fran Martin at the University of Melbourne as a preliminary step in a larger transnational comparative study of lifestyle programming in Asia in which we seek to examine the role of lifestyle television in both shaping and reﬂecting broader shifts in social and cultural identity accompanying the rise of consumer-based modes of modernity.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); Australie (lieu de production du savoir); Singapour (corpus analysé); _Nettoyé

Playing at Being Mobile: Gaming and Cute Culture in South Korea - Hjorth, Larissa (Fibreculture Journal, 2006)
This paper is based on ongoing research into the gendered use of mobile convergent media in the Asia-Pacific region. In particular, what role does the cute have and how does it correlate with types of consumption? As a region, the Asia-Pacific is marked by diverse penetration rates, subject to local cultural and socio-economic nuances. Two defining locations - Seoul (South Korea) and Tokyo (Japan) - are seen as both mobile centres and gaming centres which the world looks towards as examples of the future-in-the-present. Unlike Japan, which pioneered the keitai (mobile) IT revolution with devices such as i-mode, South Korea has become a centre for mobile DMB (Digital Multimedia Broadband) with the successful implementation of TV mobile phones (TU mobile) in 2005. One of the key features of mobile media technologies is the attempt by the industry to find the next killer application . One such application is the possibility of online multiplayer games accessed through mobile (broadband) telephonic devices such as MMO golf RPG Shot Online (a golf game for mobile phones). Amongst this frenzy of trend spotting and stargazing, Seoul as a mobile broadband and gaming centre provides a curious case study for the social and cultural intricacies informing the rise of gaming as an everyday practice for many Koreans.This article begins by outlining the game play and technoculture particular to South Korea and then explores the phenomenon of Kart Rider in South Korean gaming cultures - and its perception/ reception outside Korea - to sketch some of the issues at stake in playing it cute (particularly in the form of cute avatars), consuming Korea and the endurance of co-present communities. In particular, it contemplates the implications of current emerging online mobile gaming genres such as so-called female games such as the cute' Kart Rider in order to think about changing modes of game play and attendant social spaces.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 3-Asie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Autrice; _Nettoyé